Improving Fifth Grade Students’ Math Outcomes Using iSpring Suite 11 Media and Corner Clock Tools - Kumala, Farida Nur; Mukhlis, Muhammad Sulthon; Sulistyoningsih, Sulistyoningsih (Actual Insight, 2025)
This research investigates the improvement of mathematics learning outcomes in the angle topic among fifth-grade students at Sekolah Dasar Negeri Gadang 1 Kota Malang. Preliminary observations indicated that students' learning outcomes were still low, with an average score of 66.35 and a learning mastery rate of 42.30 percent. This condition is attributed to monotonous teaching methods and the absence of interactive media that align with students' characteristics. The purpose of this study is to enhance students' mathematics learning outcomes by utilizing iSpring Suite version 11 media combined with the use of physical angle clocks as learning aids. The research employed a classroom action research design based on the Kemmis and McTaggart model, which was implemented over two cycles within a four-week period. Each cycle comprised the stages of planning, action implementation, observation, and reflection. The participants in this study consisted of 26 students from class V B. Data collection techniques included observation, learning outcome tests, and documentation. The data were analyzed using qualitative descriptive and quantitative methods. The success criteria were defined as a minimum of 85 percent of students achieving scores above the Minimum Mastery Standard of 75. The results demonstrated a progressive increase in student learning outcomes across cycles. In the first cycle, the average score reached 75 with a learning mastery rate of 61.53 percent. In the second cycle, the average score increased to 88.08 with a learning mastery rate of 84.61 percent. These findings indicate that the application of iSpring Suite version 11 media supported by physical angle clocks is effective in improving mathematics learning outcomes.